Bicarbonate Recognition Features of a Naphthobipyrrole‐strapped Calix[4]pyrrole. (27th November 2020) - Oh, Ju Hyun; Yang, Ju Ho; Choi, Han‐Byeol; Kim, Sung Kuk
Abstract : A calix[4]pyrrole (1 ) strapped with a naphthobipyrrole was prepared and its ability to bind the bicarbonate anion (HCO3 − ) was investigated via 1 H NMR and UV/Vis spectroscopic analyses. The resulting spectral data revealed that receptor 1 was capable of recognizing HCO3 − with high affinity in solutions as well as in the solid state. In CD2 Cl2, it was inferred from 1 H NMR spectroscopic titration experiment that HCO3 − interacts with receptor 1 via two different modes with the first involving HCO3 − being hydrogen bonded to all six NH protons of the receptor. This interaction is followed by a deprotonation process of the bipyrrole NHs upon the subsequent addition of HCO3 − while the anion remains hydrogen‐bonded to the calix[4]pyrrole NHs. In the presence of methanol, the bound bicarbonate anion was converted into an unstable monomethyl carbonate anion (CH3 OCO2 − ) that was then stabilized by forming a complex with receptor 1 . Abstract : The naphthobipyrrole‐strapped calix[4]pyrrole binds the bicarbonate anion with high affinity via two sequent interaction modes.